Reading and all that jazz : - Mather, Peter (Mc Graw Hill, 2007)
Annotated Instructor's Edition. Designed to help students become jazzed about reading, this introductory-to-intermediate reading text provides motivating and engaging readings selected to grab the reader's attention. Reading and All That Jazz, Third Edition, also features clear explanations and a wide variety of well-developed practice exercises designed to provoke genuine thinking, interpretation, and even some improvisation on the part of the student and the instructor. The theme of jazz encourages a positive, exciting, personally involved approach to reading and learning.